Isolasi dan Karakterisasi Morfologi dan Fisiologi Bakteri Bacillus sp. Endofitik dari Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) - Puspita, Fifi; Ali, Muhammad; Pratama, Ridho (Jurnal Agro Teknologi Tropika, 2017)
Endophytic bacteria are bacteria that infect and live in plant tissue, including oil palm plant tissue. There are many species of endophytic bacteria living inside tissue oil palm plant which play a beneficial role for plant. One of the bacteria is Bacillus sp. Bacillus sp. can be used as a biological pesticide and biological fertilizers which is useful for plants. The purpose of the research is to observe the characteristics of the endophytic Bacillus sp. Plants samples was taken by survey method. The location of sampling was at the district of Asahan North Sumatera. Isolation was performed from oil palm plant organs such as root, stems and leaves of oil palm plants. Results showed that the morphological characterization such as colony color, colonies form and colonies edges of the bacteria had similarities each others, but there was a difference on the surface of morphology colony. Six isolates had a convex surface and six isolates had a flat surface. Physiology assay results such as catalase test, oxidase test, starch hydrolysis test, motility test and test of temperature on the growth of the bacteria showed a positive result on the each isolate. Characterization results showed a morphological and physiological similarities to the characteristics of Bacillus subtillis.